ChemInform Abstract: Cobalt‐Catalyzed Intermolecular Stereoselective Bisbenzylation of Alkynes. Issue 29 (July 2015) - Komeyama, Kimihiro; Asakura, Ryota; Fukuoka, Hiroshi; Takaki, Ken
Abstract The cobalt‐catalyzed reaction of benzyl bromides with alkynes in the presence of manganese as reductant produces cis‐1, 2‐bisbenzylated alkenes.